Longitudinal changes in the hypothalamic–pituitary–adrenal axis and sympathetic nervous system are related to the prognosis of stroke - Chen, Xu-Guang; Shi, Sheng-Yi; Hu, Lan; Chen, Yu; Sun, Han-Wen; Zhou, Lei; Lu, Zhen-Bing; Wang, Huan; Wang, Xiao-Shan; Yu, Jie; Zhao, Yu-Jia; Lu, Yi-Ming; et al. (Frontiers in Neurology, 2022)
BACKGROUND AND PURPOSE: This study sought to identify biomarkers in the neuroendocrine system related to stroke progression to improve the accuracy of traditional tools for evaluating stroke prognosis. METHODS: Seventy-four stroke patients and 237 healthy controls were prospectively included. We measured urinary epinephrine (E), noradrenaline (NE), dopamine (DA) and cortisol (F) on days 1, 3 and 5 after stroke onset and plasma F, adrenocorticotropic hormone (ACTH), thyrotropin (TSH), prolactin (PRL), follicle-stimulating hormone (FSH), luteinizing hormone (LH) and growth hormone (GH). The correlation between these hormone levels and 90-day prognosis was analyzed, their value in assessing prognosis was compared with lesion volume and National Institutes of Health Stroke Scale (NIHSS) scores using receiver operating characteristic (ROC) curves, and their correlation with conventional clinical variables was assessed. RESULTS: Levels of F, 24-h UFC, E, NE, DA and GH were significantly higher in stroke patients than in controls (P<0.01), while ACTH and TSH decreased, gradually approaching normal within 5 days of onset. Levels of E, NE, F and 24-h UFC were proportional to severity, and all gradually decreased within 5 days of onset in patients with a good prognosis and gradually increased or remained high in those with a poor prognosis. After adjustment for age, sex, NIHSS or Glasgow Coma Scale (GCS) score, F>13.6 μg/dL, ACTH>22.02 pg/mL and NE>123.5 μg/24 h were identified as risk factors for a poor prognosis 90 days after stroke (P<0.05). The combination of F, ACTH, NE, white blood cell count (WBC), Glu and HB was significantly more accurate than lesion volume (AUC: 0.931 vs. 0.694 P=0.019) and NIHSS score (AUC: 0.931 vs. 0.746 P=0.034) in predicting poor prognosis of stroke one day after onset. Hormones and traditional clinical variables were correlated to varying degrees, with NE correlating most strongly with 24-h UFC (r=0.54) and moderately positively with lesion volume (r=0.40) and NIHSS score (r=0.45). CONCLUSIONS: Stroke causes significant time-phased dynamic changes in the hypothalamic– pituitary–adrenal axis and sympathetic nervous system, and plasma F, ACTH and urinary NE levels can be used to assess stroke severity and prognosis.